2011
DOI: 10.1111/j.1365-2230.2011.04172.x
|View full text |Cite
|
Sign up to set email alerts
|

No impairment of monocyte‐derived Langerhans cell phenotype or function in early‐onset psoriasis

Abstract: BackgroundMigration of epidermal Langerhans cells (LCs) in response to the cytokines interleukin (IL)-1β and tumour necrosis factor (TNF)-α is impaired in uninvolved skin of patients with early-onset psoriasis.AimTo investigate whether this impairment is a reflection of a systemic defect in dendritic cells (DCs), using an established model of monocyte-derived LC-like cells (mLCs).MethodsCD14+ monocytes isolated from both patients with psoriasis and healthy control volunteers were cultured in a cytokine cocktai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our current findings suggest that KCs play an important role, and may be solely responsible, for the impaired LC migration observed in the PN skin in chronic plaque psoriasis. Our previous studies have shown that there is no obvious impairment of blood monocyte‐derived LCs . The implication is rather that impairment of LC migration is associated with an altered epidermal phenotype.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our current findings suggest that KCs play an important role, and may be solely responsible, for the impaired LC migration observed in the PN skin in chronic plaque psoriasis. Our previous studies have shown that there is no obvious impairment of blood monocyte‐derived LCs . The implication is rather that impairment of LC migration is associated with an altered epidermal phenotype.…”
Section: Discussionmentioning
confidence: 94%
“…Our previous studies have shown that there is no obvious impairment of blood monocyte-derived LCs. 16 The implication is rather that impairment of LC migration is associated with an altered epidermal phenotype. The data presented here are consistent with that view.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that LC migration is abnormal in psoriasis; migration is impaired following exposure to contact allergens, IL-1b or tumour necrosis factor-a, 57 stimuli that would induce migration in normal skin. 58 This effect is thought to be due to an alteration in the epidermal microenvironment, 59 rather than a systemic change in the function of the dendritic cells. Kleyn et al 56 observed in healthy volunteers that LC migration from the epidermis (identified by a reduced frequency of epidermal LCs) is triggered by acute psychological stress (Trier paradigm).…”
Section: Immune-mediated Pathwaysmentioning
confidence: 99%
“…Langerhans cells (LC), a population of epidermal dendritic cells that present antigens to T lymphocytes and orchestrate cutaneous immune responses, have been implicated in the pathogenesis of psoriasis . In normal skin the mobilization of LC requires signals from interleukin (IL)‐1β and tumour necrosis factor (TNF)‐α.…”
mentioning
confidence: 99%
“…In previous investigations we have shown that early‐onset (presenting before age 40 years) chronic plaque psoriasis (CPP) is associated with a substantial inhibition of LC migration in response to IL‐1β and TNF‐α . The view is that the impairment of LC mobilization is the consequence of abnormalities in the epidermal microenvironment …”
mentioning
confidence: 99%